A drought monitoring operational system for China using satellite data: design and evaluation. Issue 1 (2nd January 2016) - Yan, Nana; Wu, Bingfang; Boken, Vijendra K.; Chang, Sheng; Yang, Leidong
Abstract : Droughts occur frequently in China and their real-time monitoring and timely reporting are required for prevention and mitigation. This paper presents a method for developing an operational drought monitoring system for China. The method is based on various components such as Moderate Resolution Imaging Spectroradiometer data access, data processing, indices calculations, drought monitoring and analysis, and information dissemination. The system was tested by monitoring drought conditions in the early spring of 2009 in the Hai Basin of China. Results were compared with the in situ data-based indices. It was found that the system was capable of monitoring spatial variation in vegetation conditions attributed to droughts. The traditional meteorological drought index and yield data were collected to evaluate the system performance. A stronger relationship was found between the vegetation health index and the three-month standard precipitation index for the rainfed cropped areas. The relationship between the drought-area percentage and the winter wheat yield reduction percentage for 16 counties was stronger for the April–May period than for the February–March period. The drought monitoring system could explain about 60% of the variance in the winter wheat yields.